Tension release in piano playing: teaching Alexander Technique to undergraduate piano majors - Loo, Fung Ying; Evens, Gabriel Isaac; Hashim, Mohd Nasir; Loo, Fung Chiat (Elsevier, 2015)
This article explores the effectiveness of Alexander Technique in reducing tension in piano playing. Much of the literature regarding the Alexander Technique tends to be guide books for various uses targeting actors, musicians, sportsmen and so forth. There are also a growing number of alternative medical research studies that examine the effectiveness of the Alexander Technique in reducing disability in Parkinson disease, improving postural equilibrium, and relieving back pain. However in the area of music performance, little empirical research has been carried out. In this study, fifteen undergraduate piano majors from a local university in Malaysia were recruited as research subjects. Four major principles of the Alexander Technique were employed in this test. Observation was carried out and a report of tension in certain body parts was recorded. The subjects went through fourteen week of lessons taught by an Alexander Technique instructor, and a survey was carried out. The results indicate a positive outcome that Alexander Technique may help pianists to reduce tension.